Idiopathic Hypertrophic Dorsal Pachymeningitis - Imaging Features - Krishna Kumar; R. Rajalakshmi Preethi (Asian Journal of Medical Radiological Research, 2019)
Idiopathic Hypertrophic Spinal Pachymeningitis (IHSP) is a rare disease causing chronic inflammatory hypertrophy of the dura mater. It may be idiopathic or secondary to other diseases. It is an extremely rare cause of spinal cord compression. This process can be present throughout the entire spine but is commonly reported in the cervical and dorsal spine. IHSP is a diagnosis of exclusion since it is associated with trauma, infection, and autoimmune diseases. We describe a rare case of Idiopathic Hypertrophic Dorsal Pachymeningitis (IHDP) in a 42 -year -old woman presenting with progressive weakness of both lower limbs for the past 2 years and outline the important clinical and radiographic features of the disease.